Exploring factors contributing towards community’s awareness in 3R behaviour - Izyan Farhana Zulkarnain; Azlina Bujang; Saifulrizan Norizan; Sarehan Sadikin; Nur Farhani Samasu; Aiza Johari (Penerbit Universiti Kebangsaan Malaysia, 2023)
The lack of knowledge and the ineffectiveness of many Reduce, Reuse, and Recycle (3R) awareness efforts are two problems caused by human behaviour and several solutions can be identified to rectify these issues. In line with this, one 3R programme was implemented in Samarahan, Sarawak, aiming to improve the knowledge, attitude, and practise of 3R awareness among the local community. 3R is one strategy for reducing and decreasing waste production whereby the rise of recycling rates could be the indicator of 3R awareness effectiveness for both the government and voluntarily engaged individuals as well as the communities. These days, both developed and developing nations are looking for the best methods in reducing the effects of climate change and looking for the best feasible solutions. As a result, this study has explored the conceptual ideas of general public’s awareness and the factors that influence their behaviours to be involved and engaged in 3R activities. Positive information regarding these behaviours may encourage the public to accept and practise the concepts of good citizenship in Malaysia. As the government's aspiration to raise the citizen’s awareness on the values and benefits of practising 3R in their daily life are still lacking, studying the factors that influence their behaviours to conduct 3R activities is a necessity to improve the environmental awareness.